2017
DOI: 10.4254/wjh.v9.i13.613
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic complications induced by immunosuppressants and biologics in inflammatory bowel disease

Abstract: The incidence of inflammatory bowel diseases (IBD) is rising worldwide. The therapeutic options for IBD are expanding, and the number of drugs with new targets will rapidly increase in coming years. A rapid step-up approach with close monitoring of intestinal inflammation is extensively used. The fear of side effects represents one the most limiting factor of their use. Despite a widespread use for years, drug induced liver injury (DILI) management remains a challenging situation with Azathioprine and Methotre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 180 publications
(209 reference statements)
0
30
0
3
Order By: Relevance
“…Additionally, MTX damages the intestinal mucosa, thereby disrupting the intestinal barrier functionality and allowing bacterial translocation to the liver to induce hepatotoxicity (Song et al, 2006; Duman et al, 2013). The increase in intestinal permeability is positively correlated with diarrhea, and MTX-induced high permeability significantly participates in liver inflammation (Tran-Minh et al, 2017). Interestingly, Hu et al (2003) demonstrated that MgIG is mainly excreted into bile in unchanged form.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, MTX damages the intestinal mucosa, thereby disrupting the intestinal barrier functionality and allowing bacterial translocation to the liver to induce hepatotoxicity (Song et al, 2006; Duman et al, 2013). The increase in intestinal permeability is positively correlated with diarrhea, and MTX-induced high permeability significantly participates in liver inflammation (Tran-Minh et al, 2017). Interestingly, Hu et al (2003) demonstrated that MgIG is mainly excreted into bile in unchanged form.…”
Section: Introductionmentioning
confidence: 99%
“…According to a French review in 2017, biological agents may increase liver enzymes. However, their concentrations often vary slightly and return to normal values within continued treatment [27]. The results of this study suggest that changes in ALT, AST and ALP mean concentrations varied in reference ranges, when GGT concentration increased less than two-fold during the first 5 years of treatment, returning to the reference range of 33.4 mmol/L after 6 years of treatment.…”
Section: Changes In Laboratory and Instrumental Testsmentioning
confidence: 59%
“…11 Moreover, the rate of reactivation of hepatitis B and C viruses appears to be lower for tacrolimus than for systemic corticosteroids. [12][13][14][15][16] A meta-analysis assess-…”
Section: Discussionmentioning
confidence: 99%
“… 11 Moreover, the rate of reactivation of hepatitis B and C viruses appears to be lower for tacrolimus than for systemic corticosteroids. 12 13 14 15 16 A meta-analysis assessing the risk of adverse events in patients with systemic lupus erythematosus found that the rate of serious adverse events was lower for tacrolimus than for other immunosuppressants such as glucocorticoids, cyclosporine, azathioprine, cyclophosphamide, mycophenolate mofetil, methotrexate, and rituximab. 17 Tacrolimus was also suitable for controlling ocular inflammatory diseases including Behçet's disease and Vogt-Koyanagi-Harada syndrome without inducing increases in infection and malignancy.…”
Section: Discussionmentioning
confidence: 99%